On the Economy and the Ecological Ethics - Kośmicki, Eugeniusz (Anthropological Review, 1985)
The traditional paradigm of economics treating economy as an autonomics system becomes useless. There appears a new paradigm of ecological economy assuming a dependence between the economy and biosphere. The ecological ethics connected. with this economy takes into account the natural conditioning of the human existence.